Encyclopedia of geology - Selley, Richard C. 1939-; Cocks, L. R. M. (Leonard Robert Morrison) 1938-; Plimer, I. R. (Gale virtual reference library, 2005)
Covers all aspects of geology including earth history, earth materials, surface processes, regional geology, economic geology, engineering geology, petroleum geology, geochemical and mineral exploration, and the history of geology.